The Impact of Inherited Retinal Diseases in the Republic of Ireland (ROI) and the United Kingdom (UK) from a Cost-of-Illness Perspective - Galvin O (Dove Medical Press, 2020)
Orla Galvin,1 Gloria Chi,2 Laura Brady,3 Claire Hippert,4 Marta Del Valle Rubido,4 Avril Daly,1 Michel Michaelides5,6 1Retina International, Dublin 8, D08 R9CN, Ireland; 2Genentech, Roche Group, South San Francisco, CA 94080-4990, USA; 3Fighting Blindness, Dublin 2, D02 TW98, Ireland; 4F. Hoffmann-La Roche Ltd, Basel 4070, Switzerland; 5UCL Institute of Ophthalmology, University College London, London, UK; 6Moorfields Eye Hospital NHS Foundation Trust, London, UKCorrespondence: Orla Galvin Email orla.galvin@retina-international.orgAbstract: To date, there has been a global lack of data regarding the prevalence of conditions falling under the Inherited Retinal Diseases (IRD) classification, the impact on the individuals and families affected, and the cost burden to economies. The absence of an international patient registry, and equitable access to genetic testing, compounds this matter. The resulting incomplete knowledge of the impact of IRDs hinders the development and commissioning of clinical services, provision of treatments, and planning and implementation of clinical trials. Thus, there is a need for stronger evidence to support value for money to regulatory bodies for treatments approved, and progressing through clinical trials. To ensure a strategic approach to future research and service provision, it is necessary to learn more about the IRD landscape. This review highlights two recent cost-of-illness reports on the socio-economic impact of 10 IRDs in the Republic of Ireland (ROI) and the United Kingdom (UK), which demonstrate the comprehensive impact of IRDs on individuals affected, their families, friends and society. Total costs attributable to IRDs in the ROI were estimated to be £ 42.6 million in 2019, comprising economic (£ 28.8 million) and wellbeing costs (£ 13.8 million). Wellbeing costs were estimated using the World Health Organization (WHO) burden of disease methodology, a non-financial approach, where pain, suffering and premature mortality are measured in terms of disability-adjusted-life-years (DALYs). In the UK, wellbeing costs attributable to IRDs were £ 196.1 million, and economic costs were £ 327.2 million amounting to £ 523.3 million total costs in 2019. Accounting for over one-third of total costs, the wellbeing burden of persons affected by IRDs should be emphasized and factored into reimbursement processes for therapies and care pathways. This targeted review presents the most current and relevant data on IRD prevalence in the ROI and the UK, and the impacts (financial and non-financial) of IRDs in terms of diagnosis, wellbeing, employment, formal and informal care, health system costs, deadweight losses and issues surrounding payers and reimbursement. This review demonstrates IRD patients and their families have common issues including, the need for timely equitable access to genetic testing and counselling, equality in accessing employment, and a revision of the assessment process for reimbursement of therapies currently focused on the cost-of-illness to the healthcare system. This review reveals that IRD patients do not frequently engage the healthcare system and as such suggests a cost-of-illness model from a societal perspective may be a better format.Keywords: genetic diagnosis, inherited retinal disease, cost-of-illness